Book review: Organisational behaviour: A contemporary South African perspective - Andrew Thatcher (SA Journal of Industrial Psychology, 2004)
Authors: Helen Schultz (Ed.), Jeffrey Bagraim, Tracy Potgieter, Conrad Viedge, Amanda Werner Publisher: Van Schaik Publishers According to the authors the aim of this book is to present an interdisciplinary approach to the understanding of organisational behaviour within the contemporary South African environment. Within this framework, the book targets (senior) undergraduate and postgraduate students in Industrial/Organisational Psychology and Human Resources Management. The text is written in a simple, conversational style (as was the intention of the authors) that should be suitable for most undergraduate students at English-speaking tertiary institutions. The book is organised into three sections based on a model of four components of organizational behaviour: the individual, the group and the organisation. The fourth component of the model, the environment, refers specifically in the context of this book, to a contemporary South African approach to understanding behaviour in organisations. In the ‘individual’ section, the authors cover topics such as individual differences (e.g. personality, attitudes, perceptions, emotional intelligence, etc.), ethics, work motivation, and performance management. In the ‘group’ section, the authors look at issues of group and team dynamics, power and empowerment, communication, decision-making and leadership. Finally, in the ‘organisation’ section, the authors address issues of contemporary organisational design, organisational change and employee well-being (e.g. stress management, job satisfaction, etc.).